In vitro Propagation of Plectranthus bourneae Gamble? An Endemic Red Listed Plant (Plant Tissue Culture and Biotechnology, 2016)
An efficient protocol of in vitro propagation of Plectranthus bourneae Gamble (Lamiaceae), a valuable medicinal important and endemic Red listed plant of Western Ghats, (Tamil Nadu, India) was standardized by improved shoot multiplication from axillary bud explant. An in vitro propagation system has been reconnoitered on MS with the effective concentration BA (0.7 mg/l) followed by a combination of BA (0.7 mg/l) and TDZ (1.0 mg/l) which promoted high number of shoots. The multiple shoot rate was enhanced further by adding AdS (50 mg/l). Beneficial shoot length was achieved when cultured on MS containing GA3 (0.5 mg/l). Rooting was increased on MS augmented with IBA (1.5 mg/l). Micropropagated plants were acclimatized and the survival rate was 80%. Acclimatized P. bourneae plants can be used as substitute alternative to natural populations. Using this protocol the propagated plants can be used for conservation strategies.Plant Tissue Cult. & Biotech. 25(2): 273-284, 2015 (December)